Internet Addiction Syndrome (IAS) - Jakubik, Andrzej (Studia Psychologica: Theoria et praxis, 2002)
The author discusses the problem that the Internet can be as addicting as alcohol, drugs and pathological gambling or workaholism. Step by step he presents his own conception of the socalled Internet Addiction Syndrom (IAS), the controversy about the uniqueness of Internet addiction, its origin, the clinical diagnostic criteria according to DSM-IV and ICD-10, the psychological, social and somatic consequences of this type of disorder for dependent Internet users, and finally - propositions of therapy.